The Land - Use Economy of Orissa with Special Reference to Forestry - Sharma, R. A. (Indian Forester, 1993)
Forests have played a vital role in the predominantly agrarian economy of Orissa. The Orissan forests, which are subjected to heavy biotic pressure, need to be rehabilitated in order to sustain and enhance their contribution to the economy. Social forestry can help reduce the biotic pressure by creating sustainable forest resources.